Blood Collection Guidelines and Techniques in Small Laboratory Animals for Biomedical Research: A Systematic Review: Life Sciences-Medical - Port Louis, Leena Rajathy; Nagarajan, Prithiviraj; Balakrishnan Ramajayam, Asokan (International Journal of Life Science and Pharma Research, 2023)
Venipuncture, phlebotomy, or blood collection is a specific and important procedure for collecting samples from research animals. Many research techniques require multiple blood samples to analyze the data. In truth, laboratory rodents are smaller in size and have a relatively low blood volume compared to humans. Any major reduction in blood volume would have an extreme consequence on the animal’s biology. Consequently, the safe amount of blood samples that can be obtained from an animal and the frequency of safe blood collection are the two extremely important factors to consider for protecting the health and welfare of the animals. Because stress to the study animal affects the research outcome, the techniques used should allow blood sampling while diminishing the potential for pain, suffering, avoidable stress, or unexpected results in the study animal. Several regulatory bodies have issued guidelines for collecting blood from study animals. Information on general blood collection guidelines and the different blood collection sites in laboratory animal species are scattered across various literature. This review presents a consolidated data on all the guidelines and precautions involved in blood sampling from small laboratory animals. Using suitable keywords, reference documents were collected from online databases like PubMed, Embase, Scopus, Medline and Google Search. However, researchers are the better judges in choosing the right blood collection method to use in their study, keeping in mind the welfare and health of their research animals.